Generalization of some inequalities for the (q_1, . . . , q_s)-gamma function - Armend Shaban Shabani; Toufik Mansour (Le Matematiche, 2012)
Recently were established q-analogues of some inequalities involving the gamma functions. In this paper are presented the (q1, . . . , qs)-analogues of those inequalities.